Understanding the clinical and functional outcome of flexor hallucis longus tendon transfer and V-Y plasty for chronic Achilles tendon rupture: a case series - Kumar, Vicky; Kumar, Ravinder; Goyal, Devarsh; Assat , R. P. (International Journal of Research in Orthopaedics, 2026)
Chronic Achilles tendon rupture secondary to insertional Achilles tendinopathy leads to significant functional disability, and its optimal surgical management remains a topic of discussion. This prospective case series evaluated the clinical and functional outcomes of flexor hallucis longus (FHL) tendon transfer with V-Y plasty in nine patients treated between January and December 2023. Following a standardised postoperative rehabilitation protocol, functional assessment was performed using the American Orthopaedic Foot and Ankle Society (AOFAS) scoring system and ankle range of motion (ROM) at three and six months postoperatively. The mean age of patients was 49.4±7.86 years, and most were male. AOFAS scores improved significantly from 72±2.5 at three months to 92±2.3 at six months (p=0.001), and significant gains in dorsiflexion and plantarflexion were observed over the same period (p<0.001). At six months, ankle ROM of the operated limb was comparable to the contralateral side, and no clinically relevant weakness of great toe flexion was noted. These findings suggest that FHL tendon transfer combined with V-Y plasty is an effective and reliable technique for managing chronic Achilles tendon rupture due to insertional Achilles tendinopathy, resulting in meaningful restoration of function and range of motion. Further larger-scale comparative studies are warranted to confirm these results.